The impact of customer satisfaction, trust, switching costs and social media engagement on customer retention : a study of Malaysia mobile service providers - Ng, Wai Ling (2017)
As the competition is getting more and more intense in today’s business, many companies are shifting their focus from new customer acquisition to customer retention in their marketing strategies. Therefore, relationship marketing has become important especially in the service centric industry such as telecommunications. Unlike discrete-based transactions, within this industry, the company-consumer relationship is formed on contractual-based transactions; customers are required to subscribe to the service from mobile service providers to get continuance access to cellular networks for mobile services. Thus keeping the customers is crucial for sustainable and profitable business. There are many different relationship marketing campaigns implemented with the ultimate objective to retain existing customers. Thus, knowing which factors have significant impact on customer retention will produce effective results.